FACE-Q craniofacial module: Part 2 Psychometric properties of newly developed scales for children and young adults with facial conditions. Issue 9 (September 2021) - Klassen, Anne F; Rae, Charlene; Riff, Wong; Denadai, Rafael; Murray, Dylan J; Bracken, Shirley; Courtemanche, Douglas J; Bulstrode, Neil; O'Hara, Justine; Butler, Daniel; Goldstein, Jesse; Tassi, Ali; et al.
Summary: Background: The FACE-Q Craniofacial Module is a patient-reported outcome measure designed for patients aged 8 to 29 years with conditions associated with a facial difference. In part 1, we describe the psychometric findings for the original CLEFT-Q scales tested in patients with cleft and noncleft facial conditions. The aim of this study was to examine psychometric performance of new FACE-Q Craniofacial Module scales. Methods: Data were collected between December 2016 and December 2019 from patients aged 8 to 29 years with conditions associated with a visible or functional facial difference. Rasch measurement theory (RMT) analysis was used to examine psychometric properties of each scale. Scores were transformed from 0 (worst) to 100 (best) for tests of construct validity. Results: 1495 participants were recruited with a broad range of conditions (e.g., birthmarks, facial paralysis, craniosynostosis, craniofacial microsomia, etc.) RMT analysis resulted in the refinement of 7 appearance scales (Birthmark, Cheeks, Chin, Eyes, Forehead, Head Shape, Smile), two function scales (Breathing, Facial), and an Appearance Distress scale. Person separation index and Cronbach alpha values met criteria. Three checklists were also formed (Eye Function, and Eye and Face Adverse Effects). Significantly lower scores on eight of nine scales were reported by participants whose appearance or functional difference was rated as a major rather than minor or no difference. Higher appearance distress correlated with lower appearance scale scores. Conclusion: The FACE-Q Craniofacial Module scales can be used to collect and compare patient reported outcomes data in children and young adults with a facial condition.